Advantages of using Pragmatic Competence in Teaching Foreign Languages (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article analyzes the advantages of using pragmatic competence in teaching foreign languages. Pragmatic competence ensures not only grammatically correct use of the language, but also takes into account its social and cultural context. The article provides language teachers with opportunities to help students understand cultural differences and use language effectively and sincerely through pragmatic competence. The study examines the impact of pragmatic competence on the learning process and its advantages in language teaching.